Memorandum of Understanding between the Institute of Governance Studies, BRAC University and Center for Governance Studies, University of Bath (2011) - Centre for Development Studies, University of Bath; Institute of Governance Studies, BRAC University (Institute of Development Studies, BRAC University and Center for Development Studies, University of Bath, 2013)
The University of Bath through its Centre for Development Studies (CDS) and, BRAC University through its Institute of Governance Studies (IGS) (collectively referred to herein as the "Parties") have agreed to enter into this Memorandum of Understanding (Memorandum), which represents a statement of intent by the parties to work together, and outlines the basis for collaboration and joint activities in fields of mutual interest. The envisaged arrangement of the Memorandum of Understanding is not entered into a formal legal agreement and shall not be subject to a legal jurisdiction in a court of law.